The bachelor's degree in Peru: Alerts and alternative - Vegas, Martín (2000)
In 1997, at the beginning of the school year, the President of the Republic announced the creation of a new educational level, the baccalaureate. The measure was the object of numerous objections on the part of the educational community, for reasons that we will see later, but at the same time it mobilized the imagination of public opinion, which placed various expectations on the measure: it would allow direct access to the university, it would grant a labor certification. However, the specific contours of the measure are practically unknown. The national educational opinion poll taken by Foro Educativo is revealing.